An anti-influenza A virus microbial metabolite acts by degrading viral endonuclease PA - Jianyuan Zhao; Jing Wang; Xu Pang; Zhenlong Liu; Quanjie Li; Dongrong Yi; Yongxin Zhang; Xiaomei Fang; Tao Zhang; Rui Zhou; Tao Zhang; Zhe Guo; et al. (Nature Communications, 2022)
Abstract The emergence of new highly pathogenic and drug-resistant influenza strains urges the development of novel therapeutics for influenza A virus (IAV). Here, we report the discovery of an anti-IAV microbial metabolite called APL-16-5 that was originally isolated from the plant endophytic fungus Aspergillus sp. CPCC 400735. APL-16-5 binds to both the E3 ligase TRIM25 and IAV polymerase subunit PA, leading to TRIM25 ubiquitination of PA and subsequent degradation of PA in the proteasome. This mode of action conforms to that of a proteolysis targeting chimera which employs the cellular ubiquitin-proteasome machinery to chemically induce the degradation of target proteins. Importantly, APL-16-5 potently inhibits IAV and protects mice from lethal IAV infection. Therefore, we have identified a natural microbial metabolite with potent in vivo anti-IAV activity and the potential of becoming a new IAV therapeutic. The antiviral mechanism of APL-16-5 opens the possibility of improving its anti-IAV potency and specificity by adjusting its affinity for TRIM25 and viral PA protein through medicinal chemistry.